Blood-sucking arthropod of bats in urban roost in the State of Rio de Janeiro - Patricio, Priscilla Maria Peixoto; Lourenço, Elizabete Captivo; Famadas, Kátia Maria (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Patrício P.M.P., Lourenço E.C & Famadas K.M. [Blood-sucking arthropod of bats in urban roost in the State of Rio de Janeiro]. Artrópodes hematófagos de morcegos em refúgios urbanos no Estado do Rio de Janeiro. Revista Brasileira de Medicina Veterinária, 38(supl. 3):75-86, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Anexo 1, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro, BR 465, Km 7, Seropédica, RJ 23890-000, Brasil. E-mail: priscilla-patricio@hotmail.com.br The occurrence of bats in urban refuges is widely reported, mainly in the southeastern region of Brazil, but few are those that report their ectoparasites. Many of these ectoparasites are hematophagous and therefore potential transmitters of pathogens. In addition, work in refuges can increase knowledge and reveal the real species richness of ectoparasites of bats. Therefore, the objective of this study was to record ectoparasitefauna of bats that use refuges in urban areas in the State of Rio de Janeiro. Seven refuges belonging to three municipalities of the State of Rio de Janeiro, Seropédica, Nova Iguaçu and Guapimirim were sampled. The bats were captured with mists nets and accommodated in cloth sacks. They were subsequently measured, identified and classified according to gender and age. Their ectoparasites were removed with the use of fine-tipped tweezers and placed in tubes with absolute ethanol and identified using dichotomous keys. A total of 908 bats were captured, 196 recaptures (21.58%), comprising 12 species from three families. A total of 14 species of arthropod ectoparasites belonging to three orders Diptera and Siphonaptera and Hemiptera. Three species of Streblidae were added to the list of the State of Rio de Janeiro: Strebla curvata, Trichobius angulatus and Trichobius dugesii and also the extension of the distribution of T. angulatus to the Atlantic Forest. We conclude that the accomplishment of works in refuges can provide the increase of species of ectoparasites, even of hosts already studied extensively.